2021
DOI: 10.7717/peerj.10880
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane/peanut intercropping system improves physicochemical properties by changing N and P cycling and organic matter turnover in root zone soil

Abstract: Background The sugarcane/peanut intercropping system is a specific and efficient cropping pattern in South China. Intercropping systems change the bacterial diversity of soils and decrease disease rates. It can not only utilized light, heat, water and land resources efficiently, but also increased yield and economic benefits of farmers. Methods We determined soil nutrients, enzymes and microbes in sugarcane/peanut intercropping system, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 75 publications
6
18
1
1
Order By: Relevance
“…Soil Pro and DHO activities were positively correlated with TN (Figure S1), which was consistent with previous studies [31]. Soil Pro are involved in the conversion of amino acids and other nitrogen-containing organic compounds present in soil, and their hydrolysates are one of the nitrogen sources for higher plants [32]. Soil DHO participates in soil carbon cycle and promotes dehydrogenation of carbohydrates and organic acids [31].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Soil Pro and DHO activities were positively correlated with TN (Figure S1), which was consistent with previous studies [31]. Soil Pro are involved in the conversion of amino acids and other nitrogen-containing organic compounds present in soil, and their hydrolysates are one of the nitrogen sources for higher plants [32]. Soil DHO participates in soil carbon cycle and promotes dehydrogenation of carbohydrates and organic acids [31].…”
Section: Discussionsupporting
confidence: 88%
“…A single bacterium can affect a variety of enzyme activities, so it is necessary to further explore or study the functional properties of each bacterium and the mechanism of soil enzyme activities themselves [35]. It was found that the transport and metabolism of amino acids, carbohydrate transport and metabolism, and metabolism of other amino acids in the secondary functional areas were relatively high in abundance, which was consistent with previous ndings [32,36]. Furthermore, it was speculated that the relative abundance of RB41 and Candidatus-udaeobacter increased.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, co-occurrence networks have been proposed as an additional parameter to characterize microbial communities ( Barberán et al, 2012 ; Berry and Widder, 2014 ; Morriën et al, 2017 ; de Vries et al, 2018 ; Li and Wu, 2018 ; Jacquiod et al, 2020 ). Concerning IC co-occurrence network, Tang et al (2021) showed, through a shotgun metagenome analysis, that sugarcane and peanut IC increased the abundance of bacterial genes involved in organic matter turnover comparing to SC, without correlating these differences to changes in microbiota diversity. Liu et al (2021) showed differences between the co-occurrence networks between two sugarcane varieties in IC.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, attempts have been to assess the impact of IC on rhizosphere microbiota. Total microbial communities ( Taschen et al, 2017 ; Li et al, 2018 ; Gao et al, 2019 ; Liu et al, 2021 ; Tang et al, 2021 ) and specific functional guilds (e.g., ammonia oxidizing bacteria, Song et al, 2007 ; diazotrophic Proteobacteria, Solanki et al, 2020 ) from the total root systems of plant genotypes associated in IC have been analyzed. These reports evidenced that rhizosphere microbiota from IC and sole-cropping (SC) differ significantly, these differences being more strongly expressed for bacteria than for fungi ( Gong et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation